Pengembangan Buku Digital Matematika Saintifik pada Materi Persamaan Kuadrat - Nur Islah Asyhar; Asdar; Nurwati Djam’an (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2021)
This development research aims to develop valid and practical a digital mathematics book scientific on the topic of quadratic equations. This research using the ADDIE development model, which includes 5 stages: analysis, design, development, implementation, and evaluation. The research instrument used is a form of media assessment sheets by media expert and material expert to measure the validity and students and teacher response questionnaires to measure the practicality of a digital mathematics book. Respondents for the product trial are 10 students of class VIII,1. The results showed that the product satisfies validity criteria based on the assessment by material expert and media expert. The product satisfies practicality criteria based on students response are categorized as strong and teacher response is categorized as very strong.